The Effect of Talent Management and Knowledge Management on Employee Performance at TVRI Est Sumatra Province - Dewi, Aminar Sutra; Adila, Winda (Bina Bangsa International Journal of Business and Management, 2023)
This study to test talent management on employee performance totest knolege management on rmployee performance. This study was conducted at TVRI, west Sumatera Province. This type of research was quantitative. The sampling method used a total sampling of 57 saturated samples. The sources of this data are primary data and secondary data. The data analysis techniques used are validity, reliability, descriptive analysis, normality test, multicolinearity test, heteroscedasticit y test, multiple regression analysis, and t test. The results show that talent management has a positive and significant effect on employee performance and knowledge management has a positive and positive and significand effect on employee performance, it can be concluded that talent management is accepted and knowledge management is accepted